SUPPORTING STUDENTS LISTENING COMPREHENSION SKILL THROUGH METACOGNITIVE STRATEGIES - Meiga Ratih Tirtanawati; Readini Anneke Putri (Bajang Institute, 2021)
Abstract: Listening is related to the ability of vocabulary because by having and memorizing many vocabularies, listening comprehension will also increase. Therefore, the writer wants to increase the students’ listening comprehension and vocabulary mastery through the metacognitive strategies. This study has three objectives: (1) to find out how is the implementation of metacognitive strategies in listening comprehension skill (2) to find out in what ways do metacognitive strategies enhance students listening comprehension and vocabulary mastery (3) to describe the barriers found in the implementation of metacognitive strategies in listening comprehension skill. This research is qualitative research in the form of case study. The subject of this study was students of class XI IPA. Data collection is taken through observation and interview. Data is analyzed by reducing the data, display the data, and draw a conclusion. The result of the research is students of XI IPA Putri SMA Terpadu Al-Ishlah Prambon is helped in listening comprehension learning and they can improve their vocabulary using metacognitive strategies, because the metacognitive strategies deal with a plan, monitor and evaluate. Students become aware of the importance of what and how they learn and gain knowledge.